Pengaruh Perilaku Phubbing terhadap Kompetensi Interpersonal Generasi Z Pengguna Media Sosial - Kristin Rahmani; C.M. Indah Soca Kuntari; Trisa Genia Chrisantiana (Universitas Kristen Maranatha, 2024)
Internet use has changed how Generation Z exchanges ideas, learn, and even uses it to coordinate collective action. This study aims to determine the effect of phubbing on interpersonal competence in Generation Z who use social media. Respondents in this study are Generation Z, social users. The sampling technique used was purposive sampling in Generation Z in Bandung aged 18-22 years who are social media users and obtained as many as 355 respondents. The measuring tool used is the Interpersonal Competence Questionnaire (ICQ) constructed by Buhrmester, et al (1988) and the Phubbing Scale constructed by Karadag et al. (2015). Based on the simple regression analysis test calculation, the results obtained were R of .453 and R2 .205 with a significance value of .00. The conclusion of this study is that phubbing behavior has negative affects about 20,5% in the interpersonal competence of Generation Z of social media users. Suggestions from practical are aimed at Generation Z to limit the use of social media in a social environment so as not to disturb the comfort of the environment.